PENGARUH STRUKTUR AKTIVA DAN RETURN ON ASSET (ROA) TERHADAP STRUKTUR MODAL DI PT. JASUINDO TIGA PERKASA, TBK TAHUN 2008-2013 (Perusahaan yang Terdaftar di Jakarta Islamic Index) - Andri Sutira (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2021)
ABSTRACTThe purpose of this research is to evaluate the influence of asset structure and profitability on PT's capital structure. Jasuindo Tiga Perkasa period 2008-2013. The method used in this study is a descriptive verification research method with a quantitative approach. Based on the results of data analysis and discussion on the influence of asset structure, Return On Asset(ROA) on the capital structure in PT companies. Jasuindo Tiga Perkasa, then the author can draw the first conclusion from the comparison of t-hitung with t-tabel with an error rate of 5% is -t-hitung < -t-tabel (-4,839 < -2,080) so that H0 is rejected and Ha accepted. A negative t value indicates that the Asset Structure has an opposite relationship with the Capital Structure. The Sig value is less than the probability value of 0.05 which is 0.000. With a confidence level of 95%, it can be concluded that the Asset Structure partially has a significant effect on the Capital Structure. The second of the results of the comparison of thitung with ttabel with an error rate of 5% is -thitung < -ttabel (-2,432 < -2,080) so that H0 is rejected and Ha is accepted. A negative t value indicates that ROA has an indirect relationship with the Capital Structure. The Sig value is less than the probability of 0.05 is 0.024. The 95% confidence level can be concluded that ROA partially has a significant effect on the Capital Structure. The three results obtained from the comparison of Fhicalculate with Ftabel are Fcalculate > Ftabel (15,780 > 3.47), then at an error rate of 5% H0 is rejected and Ha is accepted which means both free variables simultaneously have a significant effect on the capital structure. The Sig value is less than the probability value of 0.05 which is 0.000. With a confidence level of 95% so it can be concluded that the Asset Structure and ROA simultaneously have a significant effect on the Capital Structure. Keywords: Asset Structure, ROA, Capital Structure.